2016
DOI: 10.1108/maj-07-2015-1215
|View full text |Cite
|
Sign up to set email alerts
|

Auditor choice in Italian non-listed firms

Abstract: Purpose: This paper investigates auditor choice in those Italian non-listed firms adopting the 'traditional' model of corporate governance. In Italy, non-listed firms can choose between two types of auditor: the Board of Statutory Auditors (BSA), that is, the statutory auditors, or an 'external' auditor. At the same time, a BSA conducts the administrative auditing for all companies with equity exceeding 120,000 euros.Design/Methodology/Approach: The paper estimates a logistic regression model of firm auditor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 92 publications
1
18
4
Order By: Relevance
“…Based on research conducted by [7] that audit quality significantly influences income smoothing. However, different from the research conducted by [8] that the auditor's reputation has no effect but tends to be positive towards income smoothing. This shows that there is no guarantee that Big Four Audit Firm will reduce the practice of income smoothing.…”
Section: B Audit Firm Sizecontrasting
confidence: 92%
“…Based on research conducted by [7] that audit quality significantly influences income smoothing. However, different from the research conducted by [8] that the auditor's reputation has no effect but tends to be positive towards income smoothing. This shows that there is no guarantee that Big Four Audit Firm will reduce the practice of income smoothing.…”
Section: B Audit Firm Sizecontrasting
confidence: 92%
“…This means that the longer an auditor works, this does not necessarily make it easy and correct according to the needs of the client in making a decision. Our result support [3] and [14], but opposite with [15] and [16].…”
Section: A Conclusioncontrasting
confidence: 51%
“…Matonti, Tucker, and Tommasetti () examined a broad range of agency theory variables, but only found board independence to be associated positively with the appointment of high‐quality auditors for a sample of 384 unlisted Italian firms in 2009. Similarly, Alfraih () suggested that Kuwaiti firms in 2013 were more likely to appoint high‐quality audit firms when they had a larger and more independent board of directors, the presence of a female in the board, and a separated chairperson and CEO.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%